Examining the effects of additives and precursors on the reactivity of rhodium alkyl nitrenes generated from substituted hydroxylamines - Noda, Hidetoshi; Asada, Yasuko; Shibasaki, Masakatsu (Frontiers in Chemistry, 2023)
In this study, the reactivity of the alkyl nitrenes, generated from the substituted hydroxylamine precursors, was determined using the same rhodium catalyst. The results revealed that in competitive C-H insertion experiments, the regioselectivity between benzylic and tertiary C-H bonds could be modulated by adding Brønsted acids or changing the substituents on oxygen. This study enhances our understanding of the metallonitrene structures and provides valuable insights for further development of selective N-heterocycle syntheses.